Influence of CYP2C19 Metabolizer Status on Escitalopram/Citalopram Tolerability and Response in Youth With Anxiety and Depressive Disorders - Aldrich, Stacey L.; Poweleit, Ethan A.; Prows, Cynthia A.; Martin, Lisa J.; Strawn, Jeffrey R.; Ramsey, Laura B. (Frontiers in Pharmacology, 2019)
In pediatric patients, the selective serotonin reuptake inhibitors (SSRIs) escitalopram and citalopram (es/citalopram) are commonly prescribed for anxiety and depressive disorders. However, pharmacogenetic studies examining CYP2C19 metabolizer status and es/citalopram treatment outcomes have largely focused on adults. We report a retrospective study of electronic medical record data from 263 youth <19 years of age with anxiety and/or depressive disorders prescribed escitalopram or citalopram and underwent routine clinical CYP2C19 genotyping. Slower CYP2C19 metabolizers experienced more untoward effects than faster metabolizers (p=0.015), including activation symptoms (p=0.029) and had more rapid weight gain (p=0.018). A larger proportion of slower metabolizers discontinued treatment with es/citalopram than normal metabolizers (p=0.007). Meanwhile, faster metabolizers responded more quickly to es/citalopram (p=0.005) and trended toward less time spent in subsequent hospitalizations (p=0.06). These results highlight a disparity in treatment outcomes with es/citalopram treatment in youth with anxiety and/or depressive disorders when standardized dosing strategies were used without consideration of CYP2C19 metabolizer status. Larger, prospective trials are warranted to assess whether tailored dosing of es/citalopram based on CYP2C19 metabolizer status improves treatment outcomes in this patient population.